2010
DOI: 10.1593/neo.10414
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Characterization of the Efficacy Signals Due to Selective BRAF Inhibition with PLX4032 in Malignant Melanoma

Abstract: PLX4032 has robust activity in BRAF mutated melanoma. The preclinical use of this molecule identifies criteria for its proper clinical application, describes patterns of and reasons for response/resistance, and affords insight into the role of a BRAF mutation in melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
71
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 46 publications
11
71
0
1
Order By: Relevance
“…However, in some resistant cells, such as the A2058 in our study, inhibition of phosphorylated ERK and upregulation of EDNRB still occurs in response to MAPK pathway inhibition, resulting in a more favorable response to the anti-EDNRB ADC. This is consistent with a previous study in which a number of melanoma cell lines resistant to PLX4032 upregulated the expression of melanocyte-specific markers in response to the drug (24). This same study used gene expression signatures to define a category of melanoma cell lines that maintained high levels of melanocytic antigens, relative to those with low levels.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, in some resistant cells, such as the A2058 in our study, inhibition of phosphorylated ERK and upregulation of EDNRB still occurs in response to MAPK pathway inhibition, resulting in a more favorable response to the anti-EDNRB ADC. This is consistent with a previous study in which a number of melanoma cell lines resistant to PLX4032 upregulated the expression of melanocyte-specific markers in response to the drug (24). This same study used gene expression signatures to define a category of melanoma cell lines that maintained high levels of melanocytic antigens, relative to those with low levels.…”
Section: Discussionsupporting
confidence: 88%
“…Melanoma cells appear to repress cellular markers of the melanocytic lineage via activation of the MAPK pathway (24)(25)(26)(27). To some extent, this might reflect a normal developmental process used by melanocytic precursors for lineage determination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These signatures correlate to two distinct populations of melanoma cells, one with a predominantly proliferative phenotype and the other with a predominantly invasive phenotype. Subsequent transcriptional profiling studies in melanoma cells have revealed two discrete states of differentiation (Hoek, 2007;Tap et al, 2010). The first state results in a phenotype closely resembling primary human melanocytes, while the second results in a phenotype resembling neuronal stem cells (Hoek, 2007;Tap et al, 2010).…”
Section: Insight From Gene Expression Profiling Studiesmentioning
confidence: 99%
“…Subsequent transcriptional profiling studies in melanoma cells have revealed two discrete states of differentiation (Hoek, 2007;Tap et al, 2010). The first state results in a phenotype closely resembling primary human melanocytes, while the second results in a phenotype resembling neuronal stem cells (Hoek, 2007;Tap et al, 2010). Further, melanoma cells with a proliferative phenotype tend to be in a melanocytic differentiation state, while cells which acquire an invasive phenotype tend to dedifferentiate into a neuronal state.…”
Section: Insight From Gene Expression Profiling Studiesmentioning
confidence: 99%